DAMPAK KEBIJAKAN JAPAN NEW SECURITY BILL TERHADAP HUBUNGAN KERJASAMA KEAMANAN JEPANG-AMERIKA SERIKAT - Arif, Habibul Fuadi; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Japan signed a peace treaty in September 1951 with member states of the United Nations (UN) and at the same time Japan also signed a military agreement with the U.S (Japan-U.S Security Agreement). After that the role of the Japanese military in the International World was reduced, in 2015 during the reign of Prime Minister Shinzo Abe issued a new Japanese security bill, which according to Abe, the Japanese New Security Bill had a positive impact both inside and outside the country, and also increased its role in the alliance with the United States. The United States warmly welcomed the proposal and ratification of the Japan New Security Bill, the United States hoped that by implementing Japan's Japan New Security Bill it could help put the burden on Security and Defense.This research uses Realism as the Perspective by Paul.R.Viotti and Mark V.Kauppi. Realism holds that peace is formed because of the balance of power . This research use regionalization for level of analysisby Mohtar Mas’oed. This research also use using the concept of national interest by Alex Mint and the concept of foreign policy decision-making. The sources in this study were obtained from library research and internet research. Japan's New Security bill became the first step for Japan to increase its role in the defense sector and its cooperation with the United States, due to the increasing role of the Japanese military, it made a symmetrical situation in the alliance relations between Japan and the United StatesKey words : Japan New Scurity Bill, Security, Japan, Military Cooperation.